User Experience Analysis of the Dapur Mamiwido Website Using User-Centered Design Method - Risha Mufliha Safira; Aditya Rezki Saputra; Dzaka Abiyyu Azhari; Rafid Wahyu Aditya; Amata Fami (STMIK KHARISMA Makassar, 2026)
This research analyzes user experience on the promotional website of Dapur Mamiwido, a home-based culinary business in Bogor. The applied approach was User-Centered Design, encompassing user context understanding, prototype design, and solution evaluation. Data were collected qualitatively through interviews and observations, followed by testing using the System Usability Scale. Research results show the website design improves promotional effectiveness and user satisfaction with an average SUS score of 76.92 (Acceptable/Good category), along with optimization opportunities based on actual interactions. Research results indicate the importance of adjusting UI/UX design according to user needs and preferences to drive sales conversion.